ചൈനയിലെ സിൻഡ്രല്ല - മാ, അഡലിൻ യെൻ (Green books, 2009)
Adelin Ma has written this book in a way that shakes up the reader profoundly. Through this story, she lays open the fear in a child who is being (sexually?) exploited. No one coming to fetch her from school, no one receiving her letters, no one coming to visit her, carelessness by her family in informing her of her grandfather's death, the tragic end of Pi Elty the duckling, having to wear wretched clothes, inability to return to her own house, separation from Aunty Baba; moreover an event that shocks her terribly, her own father forgetting her name..! Everything..